114 Urology Stent Recall Registry. (28th February 2022) - Narayan, P.; Wood, H.; Mukhtar, S.; Papikinos, P.
Abstract: Aim: To analyse how many stent procedures were recorded (on the stent registry tool in CERNER introduced at our busy DGH) for patients undergoing an insertion of ureteric stent, this ensures patient safety is not compromised by making sure stent(s) are removed or replaced at the right time. Method: Retrospective Collection of data for 3 months. Which was followed by intervention, and a further collection of data for 3 months after implementation of changes. Parameters collected included age, gender, stent recall registered, comments present in registry, removal date. Results: In the first loop only 32.6% of the patient had the stent recall registered on the directory. Post Intervention (IT training, Posters, presenting half audit at clinical governance) the registry rate was 59%. The most common reason for insertion was for stone, followed by longstanding hydronephrosis. It was also interesting to note that 2 patients were found who were lost in follow up and an urgent action was taken to review them. Conclusions: Cerner, which is popular in NHS trusts across UK has the feasibility of having an online stent register where the information recorded gets transferred straight to the Urology office, hence ensuring correct time of removal/ exchange of stents. Trusts across UK can develop this online registration scheme in their IT system. Developing the online registry system and encouraging this audit in all NHS trusts will significantly impact the welfare and safety of patients and reduce the economic burden of NHS in dealing with complications associated with stents.